2011
DOI: 10.1111/j.1525-1446.2011.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoke‐Free Policy and Alcohol Use Among Undergraduate College Students

Abstract: Objectives The purpose of this study was to assess attitudes and behaviors related to smoke-free policy among undergraduate student alcohol drinkers on a campus in a community with smoke-free bars. Design and Sample This was a secondary data analysis of a study in which participants completed mailed surveys assessing demographic characteristics, attitudes and behaviors related to alcohol and tobacco use and smoke-free policy (n=337). Opinion and behavior items were summarized descriptively; associations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Students in this research more affected by their belief to the outcome of the policy than their significant other in forming their attitude toward smoking prohibition, Students who don't smoke have more positive attitude than students who smoke. This finding supported the research conducted at a public university in the US (Butler, Rayens, Hahn, Adkins, & Staten, 2011). In addition, research that compared national surveys from three periods in the US also found the similar result (Gilpin, Lee, & Pierce, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Students in this research more affected by their belief to the outcome of the policy than their significant other in forming their attitude toward smoking prohibition, Students who don't smoke have more positive attitude than students who smoke. This finding supported the research conducted at a public university in the US (Butler, Rayens, Hahn, Adkins, & Staten, 2011). In addition, research that compared national surveys from three periods in the US also found the similar result (Gilpin, Lee, & Pierce, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Second, only urban secondary students were investigated and rural secondary students were not investigated. In China, the smoking rate of rural secondary school students was higher than that of urban secondary school students (Butler et al 2012). Replicating this study in rural secondary school students would be useful to assess the difference between the urban and rural students in China.…”
Section: Discussionmentioning
confidence: 99%
“…Cognition and the use of tobacco significantly affect tobacco control and smoking status (Treacy et al 2007; Guo et al 2012). The smoke-free campus policy can prevent non-regular smokers in high school from becoming regular smokers in college (Butler et al 2012). Changing the social environment through policies and decreasing exposure of non-smoking students to tobacco use may decrease smoking initiation (Ridner 2005).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Self-reported smoking rates among college students range from 9% to 25%, with rates in the United States being the highest among universities in the South. 10,11,15,19 Smoking prevention efforts such as tobacco-free policies can lead to the shifting of social norms regarding tobacco use, which include socially acceptable practices. 20 Formal policies, such as tobacco-free policies on college campuses, can enforce new behaviors through stigmatizing smoking.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other smaller studies have reflected this level of support, although current smoking status tends to reduce support and female gender consistently increases support. [10][11][12][13][14][15]19 Longitudinal studies on the impact of smoke-free campus policies have found mixed but generally positive results: one found significantly reduced smoking behavior among students on a campus with a smoke-free policy, 8 another found that strict enforcement of the policy increased policy compliance, 26 and a third found that although the policy was not effective at reducing general smoking prevalence among students, it did reduce self-reported second hand smoke exposure on campus. 9…”
Section: Introductionmentioning
confidence: 99%